2022
DOI: 10.3390/ma15093253
|View full text |Cite
|
Sign up to set email alerts
|

Snail Based Carbonated-Hydroxyapatite Material as Adsorbents for Water Iron (II)

Abstract: Carbonated hydroxyapatite (CHAp) adsorbent material was prepared from Achatina achatina snail shells and phosphate-containing solution using a wet chemical deposition method. The CHAp adsorbent material was investigated to adsorb aqua Fe(II) complex; [Fe(H2O)6]2+ from simulated iron contaminated water for potential iron remediation application. The CHAp was characterized before and after adsorption using infrared (IR) and Raman spectroscopy. The IR and the Raman data revealed that the carbonate functional grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…The dispersal leading to toxicity of Au, Ag, and graphene nanoparticles when used in water treatment is a limitation [183]. Asimeng et al [184] reported the use of CHA synthesized from snail shells as nontoxic Fe 2+ removal material from wastewater. An efficiency of 45.87 mg/g was reported compared with 2.39 mg/g for pure hydroxyapatite [185].…”
Section: Non-biomedical Applications Of Cha Nanoparticlesmentioning
confidence: 99%
“…The dispersal leading to toxicity of Au, Ag, and graphene nanoparticles when used in water treatment is a limitation [183]. Asimeng et al [184] reported the use of CHA synthesized from snail shells as nontoxic Fe 2+ removal material from wastewater. An efficiency of 45.87 mg/g was reported compared with 2.39 mg/g for pure hydroxyapatite [185].…”
Section: Non-biomedical Applications Of Cha Nanoparticlesmentioning
confidence: 99%